Caribbean vision 2020 : a regional perspective on development challenges, opportunities and strategies for the next two decades : draft - Bonnick, Gladstone ([s.n.] [S.l.], 2000)
Takes a long tern perspective view to guide actions and efforts to promote the continued economic, social and political development of the region.